2000
DOI: 10.1128/aac.44.5.1302-1308.2000
|View full text |Cite
|
Sign up to set email alerts
|

Combinations of Artemisinin and Quinine for Uncomplicated Falciparum Malaria: Efficacy and Pharmacodynamics

Abstract: Combinations of artemisinin and quinine for uncomplicated falciparum malaria were studied. A total of 268 patients were randomized to 7 days of quinine at 10 mg/kg of body weight three times a day (Q) or to artemisinin at 20 mg/kg of body weight followed by 3 (AQ3) or 5 (AQ5) days of quinine. Recrudescence rates were 16, 38, and 15% for the Q, AQ3, and AQ5 groups, respectively (P < 0.001). Recrudescence was associated with shorter parasite clearance time (PCT) and longer treatment after the blood smear had bec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
2

Year Published

2001
2001
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 16 publications
(19 reference statements)
3
22
2
Order By: Relevance
“…In a previous study, we showed that extending the duration of quinine monotherapy was equally effective in lowering P term and reducing recrudescence, as was adding a single starting dose of artemisinin before administration of quinine. 12 The critical value of P term to prevent early recrudescence was ϳ 1 parasite/L, comparable to the value found in this study.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…In a previous study, we showed that extending the duration of quinine monotherapy was equally effective in lowering P term and reducing recrudescence, as was adding a single starting dose of artemisinin before administration of quinine. 12 The critical value of P term to prevent early recrudescence was ϳ 1 parasite/L, comparable to the value found in this study.…”
Section: Discussionsupporting
confidence: 78%
“…12 In brief, P term is a simulated value, in most cases far below the detection limit. A line connecting P term and the parasite count of patients with a recrudescence represents the replication rate after treatment.…”
Section: Methodsmentioning
confidence: 99%
“…38 The parasitemia half-life of 1 hour provides a baseline for which future changes in parasite population in vivo and in vitro susceptibility profiles from this endemic area may be measured or compared, and it may be relevant in the evolution of drug resistance to the adopted ACTs. With an overall parasitemia half-life of 1 hour, it would seem likely that genuine differences occur in the parasitemia kinetics after artemisinin or ACTs administration in children from this endemic area and in patients from Vietnam (8 hours) 39 or Thailand (3 hours), 35 where the half-lives of parasitemia are considerably longer than in the present study. These differences may be related to different sampling times, different pharmacokinetic models, population variations in drug handling, and regional differences in susceptibilities in P. falciparum isolates to artemisinins and the partner drugs 36 in a region where recent data suggest that artemisinin resistance has developed.…”
Section: Discussioncontrasting
confidence: 47%
“…1 To date, resistance to QN remains particularly patchy and rare, [2][3][4][5][6][7][8][9][10][11][12] and only few cases of clinical failure have been reported in Asia and South America. The mechanism underlying QN resistance is not well-understood, and it is probably complex and multigenic.…”
mentioning
confidence: 99%